Antibacterial Activity of Essential Oils from the Leaves of Adiantum capillus Ã¢â‚¬â€ veneris Linn. - B, Victor; M, Maridass; U, Ramesh; J.M.A, Prabhu (Malaysian Journal of Science, 2003)
This paper reports on the antibacterial activity of the essential oils from the leaves of Adiantum capillus-veneris Linn. A lemon yellow colored essential oil of 0.55% v/w was extracted from the leaves by hydrodistillation. The essential oil exhibited maximum inhibitory activity against Salmonella typhi. Mild antibacterial activity was detected for Pseudomonas species., Klebsiella pneumoniae and Streptococcus pyogenes.